Functional adaptive landscapes predict terrestrial capacity at the origin of limbs - Dickson, Blake V.; Clack, Jennifer A.; Smithson, Timothy R.; Pierce, Stephanie E. (Nature (London), 2021)
The acquisition of terrestrial, limb-based locomotion during tetrapod evolution has remained a subject of debate for more than a century 1 , 2 . Our current understanding of the locomotor transition from water to land is largely based on a few exemplar fossils such as Tiktaalik 3 , Acanthostega 4 , Ichthyostega 5 and Pederpes 6 . However, isolated bony elements may reveal hidden functional diversity, providing a more comprehensive evolutionary perspective 7 . Here we analyse 40 three-dimensionally preserved humeri from extinct tetrapodomorphs that span the fin-to-limb transition and use functionally informed ecological adaptive landscapes 8 – 10 to reconstruct the evolution of terrestrial locomotion. We show that evolutionary changes in the shape of the humerus are driven by ecology and phylogeny and are associated with functional trade-offs related to locomotor performance. Two divergent adaptive landscapes are recovered for aquatic fishes and terrestrial crown tetrapods, each of which is defined by a different combination of functional specializations. Humeri of stem tetrapods share a unique suite of functional adaptations, but do not conform to their own predicted adaptive peak. Instead, humeri of stem tetrapods fall at the base of the crown tetrapod landscape, indicating that the capacity for terrestrial locomotion occurred with the origin of limbs. Our results suggest that stem tetrapods may have used transitional gaits 5 , 11 during the initial stages of land exploration, stabilized by the opposing selective pressures of their amphibious habits. Effective limb-based locomotion did not arise until loss of the ancestral ‘L-shaped’ humerus in the crown group, setting the stage for the diversification of terrestrial tetrapods and the establishment of modern ecological niches 12 , 13 . Analysis of humeri from fossils that span the fin-to-limb transition reveal that the change in the humerus shape is driven by both ecology and phylogeny, and is associated with functional trade-offs related to locomotor performance.